Unsaponifiable Matter of the Fixed Oil from the Seeds of Caesalpinia sappan Linn. - Oswal, V.B.; Garg, S.C. (Asian Journal of Chemistry, 2010)
The unsaponifiable matter (1.12%) of the fixed oil of Caesalpinia sappan Linn. has been studied for iis chemical analysis and found to consist of n-triacontane, lupeol, β-amyrin, stigmasterol, β-sitosterol and an unidentified triterpeooidal alcoholic compound.